2014
DOI: 10.3390/ijms15034031
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR-191/425 Cluster in Tumorigenesis and Diagnosis of Gastric Cancer

Abstract: Gastric cancer (GC) is among the most frequent types of cancer worldwide. Therefore, understanding the biology of GC tumorigenesis is important for appropriate diagnosis and patient surveillance. The miR-191/425 cluster has been reported to be overexpressed in various human cancers, but the tumorigenic role and clinical significance of miR-191/425 overexpression in gastric carcinogenesis is currently undefined. In this study, the expression of miR-191 and miR-425 in GC tissue and serum was assessed, and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 32 publications
3
35
0
Order By: Relevance
“…6 was conducted to make sure that our findings were not driven by any single study. After excluding seven outlier studies [21,29,39], the I 2 for heterogeneity decreased both in sensitivity (from 84.92 to 78.74 %) and specificity (from 83.00 to 77.19 %). The overall results showed only minimal changes and were similar to the original ones.…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 89%
“…6 was conducted to make sure that our findings were not driven by any single study. After excluding seven outlier studies [21,29,39], the I 2 for heterogeneity decreased both in sensitivity (from 84.92 to 78.74 %) and specificity (from 83.00 to 77.19 %). The overall results showed only minimal changes and were similar to the original ones.…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 89%
“…Because studies showed that circulating miRNAs often bind to carrier proteins or are wrapped in exosomes, they may be better protected from RNase and serve as better endogenous controls. miR-16 has been used in a variety of studies, such as studies on gastric cancer [45], adrenocortical tumors [46] and coronary artery disease [47].…”
Section: • Endogenous Controlmentioning
confidence: 99%
“…The predesigned TaqMan ® MicroRNA assays included the primer sets and TaqMan ® probe that were used. The thermal cycling conditions used for PCR were as follows: 95˚C for 10 min, followed by 40 cycles at 95˚C for 15 sec and 60˚C for 60 sec (17,18). Small nuclear U6 single nucleotide RNA (Applied Biosystems Life Technologies) was used as an internal control, and the relative expression was calculated using the comparative threshold cycle method.…”
Section: Introductionmentioning
confidence: 99%